Perencanaan Strategis Sistem Informasi Pada PT. Banter Sarana Prima Menggunakan Metode Anita Cassidy - Elin Rosliani; Sukrina Herman; Andriansyah Maulana (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2023)
PT. Banter Sarana Prima is a company engaged in the transportation and convection sector in the form of services for regular bus routes, hiace, as well as elves, rental of tourism buses and tour packages as well as convection. PT. Banter Sarana Prima requires an information system strategic plan to carry out information system management for existing information systems and information systems that will be built. The method used in information system strategic planning uses the Anita Cassidy method which can help develop business process activities in an organization which has four phases, namely the visioning, analysis, direction, and recommendation phases. The results of this study are in the form of information system strategic planning documents recommended for PT. Banter Sarana Prima for the next five years which can be used as a reference in conducting information system management.